Burn Injury-Induced Extracellular Vesicle Production and Characteristics. Issue 6 (25th June 2022) - Yang, Xiaoyuan; Chatterjee, Victor; Zheng, Ethan; Reynolds, Amanda; Ma, Yonggang; Villalba, Nuria; Tran, Thanh; Jung, Michelle; Smith, David J.; Wu, Mack H.; Yuan, Sarah Y.
Abstract : ABSTRACT: Extracellular vesicles (EVs) are nano-sized membrane-bound particles containing biologically active cargo molecules. The production and molecular composition of EVs reflect the physiological state of parent cells, and once released into the circulation, they exert pleiotropic functions via transferring cargo contents. Thus, circulating EVs not only serve as biomarkers, but also mediators in disease processes or injury responses. In the present study, we performed a comprehensive analysis of plasma EVs from burn patients and healthy subjects, characterizing their size distribution, concentration, temporal changes, cell origins, and cargo protein contents. Our results indicated that burn injury induced a significant increase in circulating EVs, the response peaked at the time of admission and declined over the course of recovery. Importantly, EV production correlated with injury severity, as indicated by the total body surface area and depth of burn, requirement for critical care/ICU stay, hospitalization length, wound infection, and concurrence of sepsis. Burn patients with inhalation injury showed a higher level of EVs than those without inhalation injury. We also evaluated patient demographics (age and sex) and pre-existing conditions (hypertension, obesity, and smoking) and found no significant correlation between these conditions and overall EV production. At the molecular level, flow cytometric analysis showed that the burn-induced EVs were largely derived from leukocytes and endothelial cells (ECs), which are known to be activated postburn. Additionally, a high level of zona-occludens-1 (ZO-1), a major constituent of tight junctions, was identified in burn EV cargos, indicative of injury in tissues that form barriers via tight junctions. Moreover, when applied to endothelial cell monolayers, burn EVs caused significant barrier dysfunction, characterized by decreased transcellular barrier resistance and disrupted cell–cell junction continuity. Taken together, these data suggest that burn injury promotes the production of EVs containing unique cargo proteins in a time-dependent manner; the response correlates with injury severity and worsened clinical outcomes. Functionally, burn EVs serve as a potent mediator capable of reducing endothelial barrier resistance and impairing junction integrity, a pathophysiological process underlying burn-associated tissue dysfunction. Thus, further in-depth characterization of circulating EVs will contribute to the development of new prognostic tools or therapeutic targets for advanced burn care.